Nursing care application of deep breath relaxation in post sectio caesarea patients with acute pain: A case study - Sari, Dea Permata; Pratami, Jesika Putri; Dewi, Rusmala; Desvita, Siti; Guhasmelanti, Veni (Science Center Group, 2025)
Background: Cesarean section often results in acute postoperative pain that may interfere with maternal recovery during the postpartum period. Effective pain management therefore becomes an essential component of nursing care to improve patient comfort and recovery outcomes. Objective: This study aimed to describe the application of nursing care using deep breathing relaxation to reduce acute pain in post–cesarean section patients. Methods: A descriptive case study design was conducted involving four post–cesarean patients in the maternity ward of Siti Fatimah Regional General Hospital Palembang in June 2025. Deep breathing relaxation therapy was implemented as a nursing intervention for two consecutive days. Data were collected through interviews, observation, documentation, and physical examination. Pain assessment was conducted using the PQRST approach and numeric pain scale before and after the intervention. Results: The findings showed that all patients experienced a reduction in pain intensity after the deep breathing relaxation intervention. Pain scores decreased from moderate levels (4–5) to 2–3 on the first day and further declined to 1–2 on the second day of intervention. Patients also demonstrated reduced behavioral signs of discomfort, improved sleep duration, and increased mobility during recovery. Conclusion: Deep breathing relaxation as a nursing intervention effectively reduces acute pain and improves comfort among post–cesarean section patients. This technique can be integrated into maternal nursing practice as a safe and effective non-pharmacological pain management strategy.